Intergranular pitting corrosion of CoCrMo biomedical implant alloy. Issue 4 (26th December 2013) - Panigrahi, Pooja; Liao, Yifeng; Mathew, Mathew T.; Fischer, Alfons; Wimmer, Markus A.; Jacobs, Joshua J.; Marks, Laurence D.
Abstract CoCrMo samples of varying microstructure and carbon content were electrochemically corroded in vitro and examined by scanning electron microscopy and electron backscatter diffraction techniques. The rate of corrosion was minimized (80% reduction from icorr = 1396 nA/cm2 to icorr = 276 nA/cm2) in high‐carbon CoCrMo alloys which displayed a coarser grain structure and partially dissolved second phases, achieved by solution annealing at higher temperatures for longer periods of time. The mechanism of degradation was intergranular pitting corrosion, localized at phase boundaries and grain boundaries of high energy (high‐angle and low lattice coincidence, Σ11 or higher); grain boundaries of lower energy did not appear to corrode. This suggests the possibility of grain boundary engineering to improve the performance of metal implant devices. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 850–859, 2014.